STEM-29. LAMINA ORGANIZATION PROMOTES MAINTENANCE OF BRAIN TUMOR INITIATING CELLS IN GLIOMA. (6th November 2017) - Lai, Sisi; Prager, Briana; Wang, Xiuxing; Rich, Jeremy
Abstract: Glioblastoma is one of the most aggressive tumors, containing self-renewing glioma stem cells (GSCs) at the apex of the tumor hierarchy that drive tumor growth. Global chromatin regulation contributes to development of the cellular hierarchy, suggesting that targeting chromatin regulators may disrupt GSCs. Nuclear peripheral anchoring of heterochromatin is mainly mediated by interactions with lamina structure Lamin A/C, Lamin B, and the inner nuclear membrane protein Lamin B Receptor (LBR). LBR mediates peripheral localization at early stages of development, and then Lamin A/C assumes tethering during terminal differentiation. Here, we report that GSCs preferentially express LBR at both the transcriptional and translational levels, whereas differentiated progeny preferentially express Lamin A/C, phenocopying developmental regulation. Interrogation of chromatin marks of active enhancer and promoters through histone 3 lysine 27 acetyl (H3K27ac) ChIP-Seq revealed stem cell specific activation peaks at LBR locus. Targeting LBR expression by RNA interference potently reduced GSC cellular proliferation, self-renewal in vitro, and tumor growth in vivo. Leveraging an in silico discovery approach based on promoter sequence analysis, we found that GABPB1 mediates upstream transcriptional regulation of LBR in GSCs. We are currently defining the specific anchored chromatin domains at the nuclear peripheral tethered by LBR required for GSC maintenance to better understand the lamina organization dependency in glioblastoma, potentially informing the development of novel targeted therapeutics.